Stomach Metastasis in a Patient with Prostate Cancer 4 Years after the Initial Diagnosis: A Case Report and a Literature Review. (1st December 2012) - Bilici, Ahmet; Dikilitas, Mustafa; Eryilmaz, Ozlem Ton; Bagli, Bekir Selim; Selcukbiricik, Fatih
Abstract : Prostate cancer commonly metastasizes bones and lymph nodes, but it very rarely spreads to the gastrointestinal tract. However, only five cases of prostate cancer metastatic to the stomach have been previously reported in the literature. We report a case of a 69-year-old man with metastatic prostate cancer who presented with upper gastrointestinal bleeding (UGB) 4 years after the diagnosis. Esophagogastroscopy revealed multiple ulcerations in the gastric body and histopathological examination confirmed gastric metastasis that originated from prostate cancer. Chemotherapy could not be given because of patient's refusal. He was treated with LHRH agonist. We suggest that for a man with prostate cancer diagnosed with UGB, stomach metastasis should be considered in the differential diagnosis of UGB.